2009
DOI: 10.1007/s10753-009-9154-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Isolated Polyphenolic and Alkaloid Fractions of Ruta graveolens L. on Acute and Chronic Models of Inflammation

Abstract: Ruta graveolens L. (Rutaceae) are traditionally used for the treatment of rheumatism, arthritis and other inflammatory conditions in the traditional medicine of India, were evaluated for their protective effect in acute and chronic models of inflammation. Carrageenan induced rat paw edema and adjuvant induced arthritis were employed as the experimental models of acute and chronic inflammation respectively. Isolated polyphenolic and alkaloid fraction (AFR) from Ruta graveolens and evaluated its anti inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
(24 reference statements)
2
19
0
1
Order By: Relevance
“…The results of the present study go parallel with results obtained by Harsha and Latha [34], they found that Methanol extract of R. graveolens showed significant anti-inflammatory activity and also provide evidence for the leaves R. graveolens in folk treatment as an anti-inflammatory agent. The results of the current study revealed the strong antiinflammatory activity of R. graveolens and are in accordance with that of the findings of Ratheesh et al [3]. They found that the alcoholic extract of R. graveolens indicated most extreme (90.9%) restraint on carrageenan incited rodent paw edema.…”
Section: Anti-inflammatory Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study go parallel with results obtained by Harsha and Latha [34], they found that Methanol extract of R. graveolens showed significant anti-inflammatory activity and also provide evidence for the leaves R. graveolens in folk treatment as an anti-inflammatory agent. The results of the current study revealed the strong antiinflammatory activity of R. graveolens and are in accordance with that of the findings of Ratheesh et al [3]. They found that the alcoholic extract of R. graveolens indicated most extreme (90.9%) restraint on carrageenan incited rodent paw edema.…”
Section: Anti-inflammatory Activitysupporting
confidence: 93%
“…R. graveolens and M. paniculata considered the most important traditional medicine in Rutaceae family [3]. They have antidiabetic, antifungal, antiandrogenic, antirheumatic pain, contraceptive, anti-hangover, antidote and insecticide effects [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Rue has been used for centuries as a medical preparation and has a variety of roles, probably because of its varied chemical composition. The chemicals in rue help decrease and reduce swelling (inflammation) (14). The extracted rue acted an inhibitory factor for growth of bacteria and this explain by the culturing of swabs taken from patient ̓ s mouth.…”
Section: Discussionmentioning
confidence: 99%
“…The components of Ruta species are of great interest in medicinal chemistry, as these compounds show a broad range of biological activity and a number of them are used in medicine. We previously reported that the alkaloid fraction from Ruta graveolens showed an anti-inflammatory effect in chronic inflammation (Ratheesh et al, 2010). Based on our previous report, this study investigates the efficacy of the alkaloid fraction isolated from Ruta graveolens in protecting oxidative damage and inflammation induced by hypercholesteromic diet in rabbits.…”
Section: Introductionmentioning
confidence: 94%